Cost-Effective and Ecofriendly Plug-In Hybrid Electric Vehicle Charging Management. Issue 1 (2017) - Kontou, Eleftheria; Yin, Yafeng; Ge, Ying-En
This study explored two charging management schemes for plug-in hybrid electric vehicles (PHEVs). The PHEV drivers and the government were stakeholders who might have preferred different charging control strategies. For the former, a proposed controlled charging scheme minimized the operational cost during PHEV charge-depleting and sustaining modes. For the latter, the research minimized monetized carbon dioxide emissions from electricity generation for the PHEVs charging, as well as tailpipe emissions for the portion of PHEV trips fueled by gasoline. Hourly driving patterns and electricity data were leveraged. Both were representative of each of the eight North American Electric Reliability Corporation regions to examine the results of the proposed schemes. The model accounted for drivers' activity patterns and charging availability spatial and temporal heterogeneity. The optimal charging profiles confirmed the differing nature of the objectives of PHEV drivers and the government; cost-effective charge should occur early in the morning, while ecofriendly charge should be late in the afternoon. Each control's trade-offs between operation cost and emission savings are discussed for each North American Electric Reliability Corporation region. The availability of workplace and public charging was found to affect the optimal charging profiles greatly. Charging control is more efficient for drivers and government when PHEVs have greater electric range.